Estimation of Genetic Superiority and Reproductive Performance of Dairy Cows at different rearing locations - Yuliati Wahyu Setyorini; Edy Kurnianto; Sutopo Sutopo; Sutiyono Sutiyono (Universitas Bengkulu, 2022)
The objective of this study was to estimate the genetic superiority using the estimated breeding value (EBV) and most probable producing ability (MPPA) and to elucidate the reproductive performance of dairy cows at two different rearing locations. This study used data from dairy cows in two areas, namely at the dairy breeding center (Group I) for 100 heads and the dairy farmers (group II) for 40 head cows. The survey method was used in this study. The parameters observed were total milk production, days open (DO), service per conception (S/C), and calving interval (CI). The data were analyzed descriptively and using a t-test. The results showed that productivity in groups I and II for the total milk production was 5,017.52±1,096.84 and 3,922.52±1,296.55 kg/head/lactation, respectively; DO was 141.45±64.30 and 281.68±92.42 days, respectively; S/C was 1.47±0.61 and 1.70±0.69 times, respectively; and CI was 421.59±63.47 and 565.23±95.33 days, respectively. In conclusion, differences in management systems in breeding center and dairy farmers group give different productivity. The results can be used for management improvement and increasing productivity strategies. Livestock selection in dairy breeding center and dairy farmers can be made by estimating the genetic superiority using the estimated breeding value and most probable producing ability.